The Imperial Mind and Biodiversity Conservation: Historical perspective on current debates in biodiversity conservation - Wright, Angus (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
Biodiversity conservation debates have recently been summarized in the phrase, “land-sparing versus land-sharing.” In the land sparing camp are those who seek policies to put as much of the earth’s surface as possible into “protected areas” in which agriculture would be virtually excluded. In order to assure adequate food production, land outside protected areas would be farmed with maximum intensity through techniques that would largely exclude or exterminate wild populations of flora and fauna. In contrast, those who advocate land sharing policies argue for a combination of protected areas alongside agricultural landscapes that would use techniques tending to favor the maintenance of wild populations within a complex matrix of land uses. Here, I contend that the attempt to settle the debate through studies that seek quantification of agricultural production data and promotion of wild species populations in existing landscapes uses is of limited value because of the inability to control properly for both temporal and spatial variation. The more fundamental problem in quantitative evaluation, the one explored at length in this paper, is that the two policy positions in fact disguise profoundly different philosophical world views that can best be understood through historical analysis of the formation of colonial and post-colonial conservation ideas and practice. I argue that the essential problem with the land-sparing perspective can be summarized in two related points: first, land-sparing strategies assume that protected areas are more protective of a broad range of species than they are; and, second, they assume that the negative effect of industrial agriculture on biodiversity is minimal and can remain so even under strategies to increase production on a smaller land base. Both of these assumptions rest on a historically derived idea of control over landscape and habitat processes that is, from the land-sharing perspective, illusory. This false sense of control over human life and ecological processes arises at least partially from a way of thinking shaped by imperialism. I lay out here a historical perspective on contemporary conservation policy debates, with emphasis on the development of conservation policy in Brazil, Meso-America, and the United States.